Comparison of the Absorbed Dose for (99m)Tc-Diethylenetriaminepentaacetic Acid and (99m)Tc-Ethylenedicysteine Radiopharmaceuticals using Medical Internal Radiation Dosimetry - Pirdamooie, Shokufeh (J Med Signals Sens, 2015)
The aim of this study was the investigation of absorbed dose to the kidneys, spleen, and liver during technetium-99 m ethylene dicysteine and technetium-99 m diethylenetriaminepentaacetic acid ((99m)Tc-EC and (99m)Tc-DTPA) kidney scan. Patients who had been prepared for the kidney scan, were divided into two groups (Groups 1 and 2). The first group (Group 1) and the second group (Group 2) received intravenous injection of (99m)Tc-EC and (99m)Tc-DTP, respectively. A certain amount of radiopharmaceuticals was injected into each patient and was immediately imaged with dual-head gamma camera to calculate the activity through the conjugated view method. Then, the doses of kidney, liver, and spleen were measured using medical internal radiation dosimetry method. Finally, absorbed dose of these organs was compared. Based on these different results (P < 0.05), organs absorbed dose was significantly less with radiopharmaceutical (99m)Tc-EC as compared with (99m)Tc-DTPA.